Surface indicators are correlated with soil multifunctionality in global drylands - Eldridge, David John; Delgado-Baquerizo, Manuel; Quero, José Luis; Ochoa, Victoria; Gozalo, Beatriz; García-Palacios, Pablo; Escolar, Cristina; García-Gómez, Miguel; Prina, Anibal; Bowker, Mathew Alan; Bran, Donaldo Eduardo; Castro, Ignacio; et al. (Wiley, 2020)
1. Multiple ecosystem functions need to be considered simultaneously to manage and protect the several ecosystem services that are essential to people and their environments. Despite this, cost effective, tangible, relatively simple and globally relevant methodologies to monitor in situ soil multifunctionality, that is, the provision of multiple ecosystem functions by soils, have not been tested at the global scale. 2. We combined correlation analysis and structural equation modelling to explore whether we could find easily measured, field-based indicators of soil multifunctionality (measured using functions linked to the cycling and storage of soil carbon, nitrogen and phosphorus). To do this, we gathered soil data from 120 dryland ecosystems from five continents. 3. Two soil surface attributes measured in situ (litter incorporation and surface aggregate stability) were the most strongly associated with soil multifunctionality, even after accounting for geographic location and other drivers such as climate, woody cover, soil pH and soil electric conductivity. The positive relationships between surface stability and litter incorporation on soil multifunctionality were greater beneath the canopy of perennial vegetation than in adjacent, open areas devoid of vascular plants. The positive associations between surface aggregate stability and soil functions increased with increasing mean annual temperature. 4. Synthesis and applications. Our findings demonstrate that a reduced suite of easily measured in situ soil surface attributes can be used as potential indicators of soil multifunctionality in drylands world-wide. These attributes, which relate to plant litter (origin, incorporation, cover), and surface stability, are relatively cheap and easy to assess with minimal training, allowing operators to sample many sites across widely varying climatic areas and soil types. The correlations of these variables are comparable to the influence of climate or soil, and would allow cost-effective monitoring of soil multifunctionality under changing land-use and environmental conditions. This would provide important information for evaluating the ecological impacts of land degradation, desertification and climate change in drylands world-wide.